2014
DOI: 10.1097/mpg.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Is Folic Acid Supplementation Really Necessary in Preterm Infants ≤32 Weeks of Gestation?

Abstract: Preterm infants receiving parenteral nutrition with high folic acid content have no risk of folate deficiency during the 2 months of age; however, preterm infants fed orally from birth with HBM or PF with a low folic acid content could be at risk for folate deficiency, especially when mothers are smokers and/or do not receive folic acid supplementation during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…FA is essential for humans and acts as a cofactor in certain biological reactions [122]; it is needed in the biosynthesis of purines and pyrimidines, for mitotic cell division, in the metabolism of some amino acids and for hystidine catabolism [49,123]. FA is involved in the modulation of one-carbon metabolism; it provides methyl donors for biosynthetic methylation of DNA and histones, influencing gene expression, neurotransmitter synthesis and restoration of DNA; it is especially important in aiding rapid cell division and growth, becoming essential for foetal development and growth [118,124].…”
Section: Folic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…FA is essential for humans and acts as a cofactor in certain biological reactions [122]; it is needed in the biosynthesis of purines and pyrimidines, for mitotic cell division, in the metabolism of some amino acids and for hystidine catabolism [49,123]. FA is involved in the modulation of one-carbon metabolism; it provides methyl donors for biosynthetic methylation of DNA and histones, influencing gene expression, neurotransmitter synthesis and restoration of DNA; it is especially important in aiding rapid cell division and growth, becoming essential for foetal development and growth [118,124].…”
Section: Folic Acidmentioning
confidence: 99%
“…potentially leading to deficiency. The most important factors influencing serum FA levels during the first month of life are maternal supplementation during gestation [125] and mother smoking [123].…”
Section: Folic Acidmentioning
confidence: 99%
“…The basal RBCFL and serum folate levels were not low in any babies. In a study conducted in Turkey, the mean serum folate level was reported as 11.5-71.7 ng/mL in 162 babies with a gestational age of ≤ 32 weeks (14). The serum folate and RBCFL levels in the study…”
Section: Discussionmentioning
confidence: 99%
“…In two studies in which babies fed with preterm formula or FBM were evaluated in terms of FA supplementation, it was reported that these babies did not require FA supplementation (14,20).…”
mentioning
confidence: 99%
“…Preterm infants receiving parenteral nutrition with high folic acid content have no risk of folate deficiency during the first 2 months of age, but infants fed orally could be at risk for folate deficiency. Micronutrient support of maternal milk and the development of modern preterm formulas for preterm infants have decreased the need for folic acid supplementation, although the practice of folic acid supplementation remains commonplace, in the absence of a systematic review to support folate supplementation in preventing anaemia of prematurity (70) .…”
Section: Folic Acidmentioning
confidence: 99%